Africanos em Francisco Beltrão: a identidade na diáspora - Rodrigues, Juliana (2017)
The text dealt with processes of identities production from a group of foreigners from African continent countries who develop work activities in a chicken processing company in Francisco Beltrão, Paraná. To assume identities is to recognize that existence develops in time and space. Considering diaspora as a destabilizing mean of an identity that is already naturally inconstant, and playing around with knowing the daily life of the other, implies a relationship of deconstruction of knowledge about the other and reconstruction of new knowledge from research experiences. This process includes listening to the other, and understanding the relationship of religion to the self-care process. In this sense, we built the Master's research: "Africans in Francisco Beltrão: Identity in the diaspora" that had as a research problem: How do the African people who reside in Francisco Beltrão have built the processes of identity and maintenance of social bond? To subsidize the research, we focus on the following questions: What is the meaning of religion, culture, for the creation of the group concept? How are the links built in the new place of life? What identity markers are triggered by subjects in the process of identity and identification? What identities do these subjects assume, which do they challenge? What factors interfere with leaving the country of origin? How is identity built in the diaspora? How does religion produce self-care and the educational process in the group? In the investigation, we selected the approach of the Case Study and used as instruments of information gathering the narrative Interviews and the record in Diário de Campo. The totality of the collected material indicated the difficulty in entering the cultural system of the Other and, likewise, the importance of such procedure to see how the processes of identity and identification in the diaspora are framed. We also have found that in these new spaces of circulation, people interact, negotiate and update conceptions and actions of identity.